Assessment of noise pullution and its impact to the citizens in Ho Chi Minh City - Tuan Anh, Nguyen; Tien Thuy, Nguyen; Thi Anh, Pham (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2022)
Noise pollution can cause health and well-being problems for people including hearing loss, stress, high blood pressure, sleep disturbances, etc. Ho Chi Minh City is the primary economic center of Vietnam. Its rapidly development, especially in recent year bring along serious noise pollution. This study assesses the current noise pollution in Ho Chi Minh City and its impact to residential areas by measuring the noise levels due the traffic; industrial and commercial activities in the urban areas. The results show that the noise pollution in Ho Chi Minh city is at alarming level. Several technical solutions has been recommended to reduce the noise level that ultimately improve life quality and further sustainable development in Ho Chi Minh City.